Episodic Sustainability Narratives & Ephemeral Awareness in Fast Fashion: Social Listening Insights - Azhar, Ratih Mukti (International Journal of Economics, Business and Innovation Research, 2026)
The discourse on sustainability within the fast fashion industry often finds itself trapped in a paradox between massive information volume and the actual depth of public engagement. This study aims to analyze the dynamics of sustainability narratives in the digital space, focusing on the phenomenon of episodic narratives and platform amplification effects. Utilizing a social listening method via the Brand24 platform, this research gathered a dataset of 19,378 mentions, reaching an accumulated digital audience of 97 million during the period of December 2025 to January 2026. The results indicate a "triple spikes" pattern, proving that public awareness of sustainability issues is episodic and unstable, with discussion volumes surging up to 29% from the baseline (693 mentions) only when triggered by viral events. Furthermore, a reach-depth paradox was identified, where visual platforms such as TikTok dominate audience reach (40%) despite having very low textual engagement (3.4% mentions). These findings confirm the occurrence of ephemeral awareness, where massive information exposure through social media only triggers momentary virtue signaling behavior without fostering sustainable changes in consumption patterns. This study recommends a strategic shift in communication from mere visual amplification toward more authentic and integrated narratives to address consumer information saturation.